A modified nutrition risk screening 2002 predicts the risk of death among hospitalized patients with COVID-19. (December 2022) - Zhang, Kemeng; Gui, Huihua; Cong, Jingjing; He, Ping
Summary: Objectives: The aim of this study was to evaluate the ability of a modified Nutrition Risk Screening 2002 (modified NRS) compared with other nutrition screening tools such as NRS 2002, Mini Nutrition Assessment Short Form (MNA-SF), and Malnutrition Universal Screening Tool (MUST) on predicting the risk of death in patients with coronavirus disease 2019 (COVID-19). Methods: We retrospectively collected data of patients who were admitted to the West campus of Union Hospital, Tongji Medical College, Huazhong University of Science and Technology between January 25th, 2020 to April 24th, 2020. The nutritional status of the patients was assessed by modified NRS, NRS 2002, MNA-SF, and MUST. According to the score of modified NRS, patients were divided into malnutrition risk group (score ≥3) and normal nutrition group (score <3). Clinical characteristics were compared between the two groups. Kaplan meier survival curve was used to analyze the difference of compositing survival rate between the two groups. The predictive efficacy of different nutritional scales on the outcome of death was detected by Receiver operating characteristic (ROC) analysis. Results: The modified NRS, NRS 2002, MNA-SF, and MUST identified malnutrition risk in 71.4%, 57.9%, 73.9%, and 43.4% of the patients, respectively. The patients were divided into malnutrition risk group and normal nutrition group by modified NRS score. Patients in the malnutrition risk group were older (65 y vs. 56 y) and with more severe and critical cases (42.30% vs. 5.20%) and diabetes cases (21.50% vs. 9.80%), worse prognosis (death of 13.80% vs. 0.50%), longer hospital stay (29 days vs. 23 days), lower albumin (31.85 g/L vs. 38.55 g/L) and prealbumin (201.95 mg/L vs. 280.25 mg/L) compared with the normal nutrition group ( P were <0.001, respectively). There were more patients with chronic respiratory disease in malnutrition risk group (9.70 vs. 2.10%, P = 0.001). BMI was lower in malnutrition risk group (23.45 kg/m 2 vs. 24.15 kg/m 2, P = 0.017). Kaplan meier survival curve demonstrated that the survival of malnutrition risk group was significantly lower than normal nutrition group ( P < 0.001). The area under the ROC curve (AUC) of the modified NRS scale (0.895) outperformed NRS 2002 (0.758), MNA-SF (0.688), and MUST (0.485). The former three scales could predict the risk of death ( P were < 0.001), while MUST could not ( P = 0.690). Conclusions: Patients with COVID-19 at risk of malnutrition have a worse prognosis than those with normal nutrition. The modified NRS scale could effectively predict the risk of death among patients with COVID-19.